Kwalifikacje i bezrobocie strukturalne w obliczu zmian technologicznych - Apolte, Thomas (Skill-biased Technical Change and Structural Unemployment in Europe, 2006)
In the introductory part of the paper the author discusses, generally and adopting a simple labor market model, the issue of remarkable differences between the US and UK on the one hand, and most continental European countries on the other, as far as employment/unemployment levels and wage structures are concerned. Particularly, he proves that the rigidity of European labor markets and their inability to adjust to structural changes in labor market consisting in outward shift in demand for skilled labor and inward shift for unskilled labor, especially by increasing differences in wages (as it was the case in the US and UK), was a main reason for growing unemployment and decreasing employment level over the last decades in continental Europe. In the following sections, more specific technical issues of interdependencies between technological change, employment and relative wages, as well as the impacts of labor market rigidities on technology shifts, have been discussed with the help of various labor market and production functions models. It includes, among other things, addressing the issue why a pretty common policy of reducing the unemployment rate by the reduction of labor supply (e.g. by lowering the retirement age) has turned out to be ineffective in most European countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 43-57